Associations of Clinical Characteristics and Etiology With Death in Hospitalized Chinese Children After Spontaneous Intracerebral Hemorrhage: A Single-Center, Retrospective Cohort Study - Huang, Xiaoyan; Cheng, Zicheng; Xu, Ye; Xia, Lingfan; Zhan, Zhenxiang; Xu, Tong; Cao, Yungang; Han, Zhao (Frontiers in Pediatrics, 2021)
Objective: We retrospectively analyzed clinical characteristics, etiology, and mortality risk factors in pediatric cases of non-traumatic spontaneous intracerebral hemorrhage. Methods: This study involved children between 29 days and 18 years old with confirmed spontaneous intracerebral hemorrhage based on head CT or MRI at the Second Affiliated Hospital of Wenzhou Medical University and Yuying Children's Hospital from January 2008 to March 2020. Demographic and clinical characteristics, etiology, imaging, and treatment data were collected at baseline. Potential risk factors of in-hospital death were identified using univariate analysis and multivariate logistic regression. Result: A total of 200 children (126 males, median age 5 years) were included in the study. Clinical symptoms of spontaneous intracerebral hemorrhage were typically non-specific (79.5%). One third of patients (31.1%) had a Glasgow Coma Scale score (GCS) ≤ 8, and nearly two-thirds (60.5%) showed a combination of ventricular hemorrhage or subarachnoid hemorrhage. Supratentorial hemorrhage was more common. Cerebrovascular disease (37.0%) and hematological disease (33.5%) were the most frequent etiologies of spontaneous intracerebral hemorrhage. Most patients (74.5%) received non-surgical treatment, while 25.5% received surgical treatment. After an average of 12 days of treatment, 167 children (83.5%) survived and 33 (16.5%) died. Multivariate logistic regression showed herniation syndrome, and low GCS (≤ 8) to be associated with increased risk of mortality, while hemorrhage due to arteriovenous malformation was associated with lower risk of mortality. Conclusion: Our data suggest that cerebrovascular disease is the most common cause of spontaneous intracerebral hemorrhage among children, and that arteriovenous malformation is associated with lower risk of death in hospital. Conversely, the presence of herniation syndrome, low GCS (≤ 8) increase risk of in-hospital mortality. Our results underscore the importance of timely imaging and supplementary examinations in cases of suspected spontaneous intracerebral hemorrhage.